POTRET PEREMPUAN DALAM TRADISI PEMINANGAN NEMU ANAK (Studi Kasus Di Kecamatan Margomulyo Kabupaten Bojonegoro) - Syahid Ahmad Faishol; Mufidah C. H.; Suwandi Suwandi (Universitas Muhammadiyah Ponorogo, 2022)
This research describes women in the tradition of proposing to find a child in the Mergomulyo community. This tradition is believed to be able to perpetuate domestic relations. On the one hand, this tradition is considered to be detrimental to women because of the anomaly of norms in its implementation. The research focus is on the position of women in the tradition of finding children from a feminist perspective. And the existence of women in the tradition of finding children from the perspective of Peter Burger's social construction. this type of empirical research using descriptive qualitative approach, data obtained by observation and semi-structured interviews with perpetrators of finding children. The results of this study show that the position of women's sexuality is entangled in established patriarchal cultural values. Male dominance is very thick. Women are sexually marginalized and do not have a role and decision in enjoying their reproductive rights because of the hegemony of men in the name of tradition. This phenomenon tarsus is maintained because it has been massively constructed. Marked by the moment of externalizing oneself with the socio-cultural world, it is marked by an adjustment to the values in the tradition which are conditions for patriarchal culture. moment of objectivation, institutionalization and habitualization in this traditional process played by male agents. Moment of Internalization, which is self-identification in the sociocultural world, women assess the social reality of the tradition to be a subjective and true reality. This shows that women's actions, roles and abilities in making objective decisions have blurred over the dominance of patriarchal cultural values.